Crimes Ambientais: responsabilidade na salvaguarda do meio ambiente - Lima, Merilande Rodrigues Fonsêca (2009)
Human societies by appropriating and extract natural resources, and adding the accumulated debris has intensified deeply affecting the environment and damage the atmosphere, land and especially water. Environmental damage such as environmental crimes typified by Law 9605/98, Law on Environmental Crimes. This research analyzes the ways in which we develop awareness of urban environmental protection in relation to compliance with the Environmental Crimes Act in the municipality of Caiçara-PB, based on the law and the testimony of the community. Study the interrelationships between education and the environment; Discuss Public Policy Environment and describe the processes of environmental preservation. The theoretical aspects were based on: education and environment, Panorama and environmental degradation, Environmental Public Policy, principles and legal aspects and the perception of environmental protection: environmental crime and documentary evidence. Methodologically classified as a case study. The techniques for data collection, were the indirect documentation: Information retrieval and bibliographic and direct - intensive participant observation and extensive - interview with questionnaire. For data processing, analysis, qualitative and descriptive. Resulting in the diagnosis: the impact of environmental crimes dump waste, residential sewage, hospital pens, cheese, slaughterhouse, tannery, charcoal, removal of sand, animal husbandry and dead animals, fences and planting of grass and removal of forest, all intended to Curimataú river. These was made photographic and geographic mapping. In addition to cases arising from allegations of environmental degradation: a Criminal Action promoted by the Public Prosecutor against six people, for the extraction of sand from the river without legal license, for which they were penalized to plant tree seedlings eighteen regional, municipality and a Civil Action filed by public prosecutors on the garbage disposal and release of the tributaries of the River Public Slaughterhouse, by which the management of the city was penalized to suit the current guidelines for operation, but such practices still in evidence. The finding of contamination of the river, the presence of fecal coliforms, using microbiological analysis of water. 59% of respondents indicated that riparian, water users of the river are likely to purchase some type of disease, 56.5% have ever received guidance about environmental preservation, except 43.55% that claimed to have knowledge through educational work of the children; most showed the total ignorance of the Environmental Law and what is environmental crime, environmental damage by synthesizing the dirt in the river and the Law of Environmental Crimes Act to "prohibit the felling of trees and deforestation, 77% perceive changes in physical aspect of the river, the city has the Organic Municipal Law, but has the Municipal Environment, Municipal Council for Environmental Education and lack of environmental education projects.